Learning Strategies of Arabic Teachers at Insan Cendekia State Islamic Senior High School (MAN IC) in Kalimantan - Fattah, Mustamin; Sayuri, Sayuri; Murdani Z, Edy (Lembaga Penelitian dan Pengabdian kepada Masyarakat, UIN Sultan Aji Muhammad Idris Samarinda, 2022)
This study aimed to investigate Insan Cendekia State Islamic Senior High School (MAN IC) as a pioneering madrasah in integrating religious and scientific knowledge under the Ministry of Religious Affairs. In this context, improving Arabic learning quality for students was continuously pursued to enhance the tool knowledge capacity in Islamic studies as a goal of IMTAQ. The study examined the learning strategies of Arabic teachers at MAN IC in Kalimantan, the characteristics of Arabic learning, and supporting and inhibiting factors. A qualitative method was used, and data were obtained through observation, interviews, and documentation. The results showed that MAN IC Kalimantan used various strategies, including mubasyarah, language skills, grammatical instructions, and drill methods. Schools had diverse learning characteristics, such as peer tutors and teachers serving as facilitators of non-formal learning. The supporting factors included the availability of media, the dormitory system, and additional lessons. Meanwhile, inhibiting factors in implementing strategies included students' educational backgrounds and the COVID-19 pandemic.